Análise, escuta e interpretação musical: o uso da análise computacional de gravações no processo de construção interpretativa de Tetragrammaton XIII, de Roberto Victorio - Rosa, Renato Mendes (2015)
In this dissertation, I discuss the analysis of recorded performances as a tool in the process of creating a musical interpretation. Considering that interpretation is traditionally based on the understanding generated by the musical score, one may question the representational limitations of notation. In this process, as notation imposes challenges to performers, listening plays an important role in enabling the creation of a musical interpretation. The proposed object departs from the hypothesis that the analysis of recorded performances with computational tools may help in the process of deciphering the musical écriture integrated to the listening of the sound phenomenon. The use of software as a resource for analyzing recorded performances approaches the intrinsic aspects of sound, which can assist the performer in understanding sonic-musical materials that are otherwise obscured by notation thus allowing a musical interpretation based on listening. The analysis of the recordings provides quantitative data about the expressive aspects of performance, such as timing, dynamics and articulation. The roots of this analytical model in the musicological field are mentioned, especially the concept of music as performance. In order to make this study possible, I adopt the work Tetragrammaton XIII for solo guitar, by Roberto Victorio, as an interpretative and analytical object. Three recordings that I made are presented in this research - two preliminary and one concluding. Based on the analysis of the two preliminary recordings, an interpretative map was elaborated as a result of the process experienced in this research, which supported the performance in the concluding recording. This recording, in turn, is understood as one performance among the many possible ones made viable by the interpretative map. Finally, I seek to understand, from this experience, to what extent the analysis of recordings may foster the expansion of listening and help to create an interpretative understanding of the work.